2021
DOI: 10.1037/pha0000498
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of measures of protective behavioral strategies across various risk factors and associated PBS-related interventions.

Abstract: Harm reduction is a framework that places substance use on a spectrum from total abstinence to continued controlled use. Protective behavioral strategies (PBS) are a set of individually implemented harm reduction strategies that have shown to reduce the rate of use and severity of consequences from risky behaviors. Previous research has shown that PBS use effectively reduces negative consequences. The present study provides an overview of the literature on PBS measures for various risk behaviors, and common in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 120 publications
0
41
0
10
Order By: Relevance
“…Several interventions, across multiple behavioural outcomes, have used PBS as an intervention target (see Peterson et al, 2021). Recent research has utilized deviance regulation theory, a social psychological theory, to increase PBS use and subsequently decrease alcohol use and alcohol-related consequences (Dvorak, Pearson, Neighbors, & Martens, 2015;Dvorak et al, 2016;Dvorak, Troop-Gordon, et al, 2018).…”
Section: Protective Behavioral Strategiesmentioning
confidence: 99%
“…Several interventions, across multiple behavioural outcomes, have used PBS as an intervention target (see Peterson et al, 2021). Recent research has utilized deviance regulation theory, a social psychological theory, to increase PBS use and subsequently decrease alcohol use and alcohol-related consequences (Dvorak, Pearson, Neighbors, & Martens, 2015;Dvorak et al, 2016;Dvorak, Troop-Gordon, et al, 2018).…”
Section: Protective Behavioral Strategiesmentioning
confidence: 99%
“…PBS are specific harm-reduction behaviors that individuals can use, while engaging in risky activities, in order to reduce and/or eliminate risks inherent to the activity (Peterson et al, 2021). For alcohol, these behaviors tend to fall into three broad categories (Pearson et al, 2012).…”
Section: Pbsmentioning
confidence: 99%
“…In contrast, SHR is often linked to problems, but not consumption (Pearson, 2013). Thus, although some PBS interventions have examined PBS as a single construct (see Dvorak, Troop-Gordon, et al, 2018; Martens et al, 2013), it has been suggested that interventions targeting PBS examine each subscale independently, rather than using a combined single construct (Peterson et al, 2021).…”
Section: Alcohol Norms Among Ftic Studentsmentioning
confidence: 99%